Implementation of the Law on the Role of Prosecutors as Corruption Crime Investigation Officers - Alendra, Alendra (PT Inovasi Pratama Internasional, 2024)
Corruption is a reality of human conduct in social interactions, considered to be deviating and endangering society and the state. The research conducted is normative-legal, that is, research that uses law as a basis for solving the problems posed, and empirical-legal research through the conduct of interviews. The data used is secondary data and the data collection methods used in this study are library surveys and field surveys. The analysis of data used is qualitative data. Based on the findings, it is believed that the Anti-Corruption Commission can only investigate cases of corruption offenses that have affected state apparatus and have resulted in state financial losses of at least billion rupiah, for this reason the role of prosecutors as investigators in criminal cases is required. Corruption that does not meet the requirements for investigation by the Anti-Corruption Commission. Legal and Non-Judicial Constraints Are Limiting Factors in Corruption Crimes Investigations